1905 W. Va. Acts 70, ch. 3, § 46. - (:unkn) unknown (My University, 1905)
The council shall have power to pass ordinances prohibiting the firing of guns, crackers, roman candles, sky-rockets, or any other fireworks, or the throwing of fire balls, or the firing of any other combination of gunpowder or other combustible or dangerous material within the city. . .
Keywords: DISCHARGE